2019
DOI: 10.1021/acs.jcim.9b00807
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Predictive Modeling of Glass Transition Temperatures: A Case of Polyhydroxyalkanoate Homopolymers and Copolymers

Abstract: Polyhydroxyalkanoate-based polymersbeing ecofriendly, biosynthesizable, and economically viable and possessing a broad range of tunable propertiesare currently being actively pursued as promising alternatives for petroleum-based plastics. The vast chemical complexity accessible within this class of polymers gives rise to challenges in the rational discovery of novel polymer chemistries for specific applications. The burgeoning field of polymer informatics addresses this challenge via providing tools and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 82 publications
1
94
0
Order By: Relevance
“…29,30 As an added challenge, the field of polymer science lacks a standardized data schema for reporting polymer structure and properties that contextualize the underlying measurement and its output. [31][32][33] Applications of ML in polymer science, therefore, have mostly been isolated to a small subset of commonly reported properties [34][35][36] or relied on legacy data collected within a single research group. [37][38][39] In a seminal report, Pruksawan et al demonstrated the utility of synthesis and property evaluation of 42 epoxy adhesive samples and employed ML to generate a predictive model that accurately described the performance of 256 possible formulations.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 As an added challenge, the field of polymer science lacks a standardized data schema for reporting polymer structure and properties that contextualize the underlying measurement and its output. [31][32][33] Applications of ML in polymer science, therefore, have mostly been isolated to a small subset of commonly reported properties [34][35][36] or relied on legacy data collected within a single research group. [37][38][39] In a seminal report, Pruksawan et al demonstrated the utility of synthesis and property evaluation of 42 epoxy adhesive samples and employed ML to generate a predictive model that accurately described the performance of 256 possible formulations.…”
Section: Introductionmentioning
confidence: 99%
“…There are several advantages of the feature representation adopted in this work. The use of polymer repeat units is more reasonable than that of monomers as the former is a building block of the corresponding polymers, though the use of polymer monomers has been widely adopted in polymer informatics [ 39 , 87 , 88 ]. This is probably due to the requirements of cheminformatics packages on the SMILES strings that can be processed.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of using different representations on T g estimation has been demonstrated through systematic representation evaluation 72 or separate model development. [37][38][39]42,43,[50][51][52][53][54][55][56][57] In addition, the development of new representations remains critical for the development of high-performance ML models. To carry out a thorough study considering different types of representations, we explore three types of feature representation based on the SMILES notation of each polymer: molecular descriptors, Morgan fingerprints, and images, as presented in Figure 2.…”
Section: Accessmentioning
confidence: 99%